2014
DOI: 10.1053/j.gastro.2013.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Interferon- and Ribavirin-Free Regimen of Daclatasvir, Asunaprevir, and BMS-791325 in Treatment-Naive Patients With HCV Genotype 1 Infection

Abstract: In a phase 2a study, the all-oral, interferon-free, and ribavirin-free regimen of daclatasvir, asunaprevir, and BMS-791325 was well tolerated and achieved high rates of SVR12 in patients with HCV genotype 1 infection. Further studies of this regimen are warranted. ClinicalTrials.gov, number NCT01455090.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(169 citation statements)
references
References 31 publications
9
160
0
Order By: Relevance
“…A proof-of-concept clinical trial of triple-DAA treatment (10) also showed that SOF&DCV&SMV can achieve a high SVR rate, while reducing the treatment period from 12 wk to only 3 wk using a response-guided protocol. Our analysis clearly supports a clinical advantage for triple-DAA-based IFN-free treatments as discussed elsewhere (8,10,(20)(21)(22).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…A proof-of-concept clinical trial of triple-DAA treatment (10) also showed that SOF&DCV&SMV can achieve a high SVR rate, while reducing the treatment period from 12 wk to only 3 wk using a response-guided protocol. Our analysis clearly supports a clinical advantage for triple-DAA-based IFN-free treatments as discussed elsewhere (8,10,(20)(21)(22).…”
Section: Resultssupporting
confidence: 83%
“…Triple-DAA IFNfree combinations are being clinically evaluated to seek more rapid and efficacious elimination of HCV, including NI&N-S5AI&PI and NI&NS5AI&NNI (8,(20)(21)(22). However, it is not yet understood how much advantage triple-DAA treatment can provide over double-DAA treatment, and which triple-DAA combination will give the best treatment outcome (8,(20)(21)(22). Here, we quantified the anti-HCV activity of eight candidate combinations of triple-DAA treatment; SOF with NS5AI (DCV, LDV) plus PI (SMV, ASV) or NNI (VX, DAS) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GT-1a-and GT-1b-infected patients (23 of 26) treated with a combination of BMS-791325 (75 or 150 mg twice daily) plus pegylated interferon ␣ and ribavirin achieved sustained virologic response, a milestone strongly associated with the cure of HCV (8). In a more recent Phase 2 study, 63 of 66 HCV-infected GT-1 patients treated for 12 or 24 weeks with a combination of BMS-791325 (75 or 150 mg twice daily), daclatasvir (60 mg once daily), and asunaprevir (200 mg twice daily) achieved sustained virologic response (9). The preclinical profile of BMS-791325, including potent activity in GT-1a and -1b enzyme and replicon assays (IC 50 and EC 50 values of 0.7-4 nM), selection of significant resistance at a single substitution site, and a robust pharmacokinetic profile in animal models, anticipated the strong antiviral effect observed in patients (10,11).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…51 Based on a modified intent-to-treat analysis, 92% of the patients achieved an SVR12. Results of an expansion cohort evaluating this triple DAA regimen in a larger number (n ¼ 166) of therapy-naïve patients including cirrhotic patients were presented at AASLD 2013.…”
Section: Clinical Trials Investigating Triple Daa Combination Therapiesmentioning
confidence: 99%